La transformación docente en tiempos de pandemia. Una mirada a los espacios de formación integral: diálogo de saberes y cine foro (Memorias Sifored - Encuentros Educación UAN, 2022)
The role of the teacher has been transformed according to the needs of the different educational contexts due to the pandemic situation. Therefore, the teacher explored and updated the use of some technological tools to optimize the teaching and learning process of pedagogical training. In accordance with this, MEMORIAS hotbed research, attached to the Faculty of Education, and with national allies such as the Todos a Aprender Program and the Externado de Colombia University led two academic spaces with the aim of encouraging critical reflection on various educational problems. The first, Knowledge Dialogue, and the second, Educational Film Forum. Thus, the group selected various themes and films that showed the impact of the teacher’s role. The research shows that both scenarios were well received and became didactic tools to encourage critical thinking in the educational community in general.
Keywords: teacher´s rol; virtual education; film forum; meta didactic; critical thinking